KETERAMPILAN MANAJERIAL KEPALA SEKOLAH DALAM MENINGKATKAN KOMPETENSI PEDAGOGIK GURU SMA NEGERI 1 SUKOREJO KABUPATEN KENDAL: KETERAMPILAN MANAJERIAL KEPALA SEKOLAH DALAM MENINGKATKAN KOMPETENSI PEDAGOGIK GURU SMA NEGERI 1 SUKOREJO KABUPATEN KENDAL - Rulianah, Nita; Nurkolis, Nurkolis; Sumarno, Sumarno (ITB AAS Indonesia Surakarta, 2025)
This study discusses the principal's managerial skills in improving the pedagogical competence of teachers at SMA Negeri 1 Sukorejo, Kendal Regency. The background of the research is the continuous improvement of teacher pedagogical competence in the Education Report at SMA Negeri 1 Sukorejo from 2022 to 2024. This achievement is estimated to be due to the principal's managerial skills. The study uses a qualitative approach with a descriptive type. Data collection uses interviews, observations and documentation. Informants are determined purposively, data was obtained through data reduction, data presentation, and drawing conclusions. The validity of the data is tested through triangulation techniques. The results of the study indicate that the principal of SMA Negeri 1 Sukorejo uses conceptual skills to improve teacher competence by understanding the concept of pedagogical competence. The principal develops strategies, through training, workshops, monitoring, observation, and involving competent resource persons. The policies taken include providing facilities, giving awards, and collaborating with other educational institutions. The principal recognizes opportunities and problems related to teacher pedagogical competence through needs analysis and routine evaluation. The principal improves teacher competence by applying human relations skills, such as building good communication, providing assistance and guidance as needed, motivating and inspiring teachers, and involving various parties in decision making related to training. In addition, the principal also uses technical skills by directing teachers in preparing learning designs, creating a comfortable and conducive classroom environment, conducting learning evaluations appropriately, and managing facilities and infrastructure in a structured manner. Teacher direction and coaching through mentoring are also carried out to ensure that the quality of learning is maintained. The conclusion of this study, the principal of SMA Negeri 1 Sukorejo applies conceptual skills, human relations skills and technical skills in improving teacher pedagogical competence. The author provides suggestions for the principal to improve monitoring and observation of the implementation of teacher pedagogical competence through academic supervision at least twice in each semester.